The utilisation of online alternative media and its implications towards participatory democracy: A Malaysian case / Azlina Kamaruddin - Kamaruddin, Azlina (Institute of Graduate Studies, UiTM, 2016)
This study examines the utilisation of online alternative media and its implications towards participatory democracy. Since the enactment of the Communication and Multimedia Act 1999, online alternative media such as Malaysiakini, Malaysia Today, and the Malaysian Insider have played a pivotal role in many political events including the post-Mahathir-Anwar political crisis, the 2008 financial crisis, election campaign, Anwar’s sodomy case, and Dr. Hasan Ali’s disclosure of PAS weaknesses. Online alternative media assist in spearheading some other relevant issues that reflect the undercurrent of discontentment or otherwise the participation of peoples’ voices towards democracy. Dissident voices become aloud without fear to voice out their opinions and dissatisfaction on political issues via online alternative media. Indirectly, it forms a force for a shift of democratic paradigm. Among others this study has explored the role of online alternative media and answered the enquiry of how Malaysians have utilised it for participatory democracy…